Taxonomy and phylogeny of the genus Lappula Moench (Boraginaceae) in North America - Rolfsmeier, Susan J. (Kansas State University, 2012)
The genus Lappula Moench is a diverse group of herbaceous plants in the large, cosmopolitan family Boraginaceae. Over sixty species are recognized in Eurasia; many are found in cold deserts, steppes, and semi-deserts of Central Asia. Fewer species were described from western North America, and compared with the Asian species they are poorly known. Various North American taxa have been placed into synonomy under Eurasian species, and complex patterns of variation have made species circumscription challenging. The goal of this dissertation was to explore phylogenetic relationships between North American and Eurasian species and to revise the taxonomy of the North American species. A molecular phylogenetic study was initiated in order to infer patterns of relationships among the North American species relative to Eurasian diversity. Samples were collected from throughout the western United States and from Siberia. Additional samples of Eurasian species were taken from herbarium specimens. Sequences were generated for three DNA regions (the ITS region of the nuclear ribosomal DNA, and chloroplast intergenic spacers trnS-trnG and rpl32-trnL) and phylogenies were generated using parsimony and Bayesian analyses. Results were in general agreement among all analyses. The genus Lappula was recovered as a monophyletic group, with the exception of the morphologically anomalous L. sessiliflora (Boiss.) Gürke, which was sister to the genus Rochelia Rchb. The native North American species of Lappula and L. redowskii (Hornem.) Greene formed a clade. Samples of L. squarrosa (Retz.) Dumort., a Eurasian steppe plant with a wide introduced range in North America, grouped with samples from Eurasia. Sampled species of Hackelia Opiz, a genus sometimes treated as part of Lappula, formed a clade separate from the Lappula species sampled here. Herbarium and field studies resulted in a revised taxonomy for the North American Lappula. Nomenclatural problems were resolved; nine native species and four varieties were recognized along with the introduced Eurasian species L. squarrosa.
Keywords: Boraginaceae; Lappula; Taxonomy; Phylogenetics; Biology (0306); Plant Sciences (0479)